(untitled) (Tri-Chandra Journal of Anthropology, 2024)
This research paper principally explores the intricate relationship between motor road development and social dynamics, aiming to understand how the construction of these roads influences local perceptions, societal images, and unintended consequences. In addition to the physical aspects of the motor road, this study examines the socio-cultural backdrop linked with road construction, delving into diverse accounts and historical narratives recounted by residents of the regions where the road was constructed. These roads represent dual symbolism of “bikas” (development) and “dukha” (hardship), mirroring the experiences and aspirations of the local inhabitants. The government, pursuing its own interests, takes on the task of road construction, revealing a complex interplay with the people living in these areas. This research article further uncovers the contrasting dynamics between the state and the community during the road construction process, shedding light on the disparities between the promises made and the realities of motor road development that unfold the political economy of road building. To conduct this written analysis of the motor road project, primary data was gathered through a three-month ethnographic field study carried out between August and October 2017 followed by several field visits till 2023. This approach included engaging in participant observation, conducting twenty comprehensive interviews with key informants, and having thirty informal discussions with participants involved in the research. Secondary data was obtained from archives, government records, and existing literature.